THE INFLUENCE OF BUSINESS LOCATION AND STORE ATMOSPHERE ON PURCHASING DECISIONS IN RUANG NAMU COFFEE & EATERY - Fadikha Fahruriza; Deni Adha Akbari (Politeknik Negeri Bengkalis, 2022)
This research is a type of quantitative research with a data collection method using a questionnaire. The population used in this study was consumers of Ruang Namu Coffe & Eatery with a total sample of 110 respondents, using a simple random sampling technique. In this study, the analysis method used was multiple linear regression. Then based on the simulates test obtained, it can be found that the independent variables of business location (X1) and store atmosphere (X2) simultaneously have a significant influence on purchasing decisions (Y) with a Fhirung > Ftabel score of 84,830 > 0.08 with a significance value of 0.000 < 0.05